Do Shareholder Rights Affect the Cost of Bank Loans? - Chava, Sudheer; Livdan, Dmitry; Purnanandam, Amiyatosh (Review of Financial Studies, 2009)
[Using a large sample of bank loans issued to U. S. firms between 1990 and 2004, we find that lower takeover defenses (as proxied by the lower G-index of Gompers, Ishii, and Metrick 2003) significantly increase the cost of loans for a firm. Firms with lowest takeover defense (democracy) pay a 25% higher spread on their bank loans as compared with firms with the highest takeover defense (dictatorship), after controlling for various firm and loan characteristics. Further investigations indicate that banks charge a higher loan spread to firms with higher takeover vulnerability mainly because of their concern about a substantial increase in financial risk after the takeover. Our results have important implications for understanding the link between a firm's governance structure and its cost of capital. Our study suggests that firms that rely too much on corporate control market as a governance device are punished by costlier bank loans.]